2021
DOI: 10.1186/s13756-021-00998-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-prescriptionxx antibiotic use for people aged 15 years or older for cough in China: a community-based survey

Abstract: Background Non-prescription antibiotic use at community is a main driver of antimicrobial resistance. Cough is a common condition and prevalent in all townships, including China. This study aims to investigate the non-prescription antibiotic use for cough in China and explore to which extent antibiotic use knowledge was correctly instructed in communities. Methods A probability-proportionate-to-size sampling method was adopted to survey from all 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Of the 53 studies containing a quantitative component, 18 studies ( 22 , 42 , 52 – 54 , 63 67 , 75 , 78 , 96 101 ) analyzed the care-seeking behavior of URTI patients ( Table 2 ), 24 studies ( 22 , 43 , 44 , 52 , 55 , 56 , 58 , 64 , 68 , 75 , 91 , 93 , 96 99 , 102 108 , 114 ) reported public expectations/demand for antibiotics for URTIs ( Table 3 ), 19 studies ( 58 , 67 , 69 – 72 , 75 , 78 , 96 98 , 100 , 101 , 106 , 108 111 , 114 ) documented antibiotic self-medication (including leftover antibiotics and those purchased without a prescription) for URTIs ( Table 4 ), eight studies ( 57 59 , 67 , 75 , 98 , 106 , 114 ) described the non-adherence of the public to antibiotic treatments ( Table 5 ), and 10 studies ( 45 , 46 , 67 , 79 , 80 , 106 , 112 114 , 118 ) surveyed the public's overall irrational use of antibiotics ( Supplementary File S5 ). Another six studies ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 53 studies containing a quantitative component, 18 studies ( 22 , 42 , 52 – 54 , 63 67 , 75 , 78 , 96 101 ) analyzed the care-seeking behavior of URTI patients ( Table 2 ), 24 studies ( 22 , 43 , 44 , 52 , 55 , 56 , 58 , 64 , 68 , 75 , 91 , 93 , 96 99 , 102 108 , 114 ) reported public expectations/demand for antibiotics for URTIs ( Table 3 ), 19 studies ( 58 , 67 , 69 – 72 , 75 , 78 , 96 98 , 100 , 101 , 106 , 108 111 , 114 ) documented antibiotic self-medication (including leftover antibiotics and those purchased without a prescription) for URTIs ( Table 4 ), eight studies ( 57 59 , 67 , 75 , 98 , 106 , 114 ) described the non-adherence of the public to antibiotic treatments ( Table 5 ), and 10 studies ( 45 , 46 , 67 , 79 , 80 , 106 , 112 114 , 118 ) surveyed the public's overall irrational use of antibiotics ( Supplementary File S5 ). Another six studies ...…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the overall prevalence of antibiotic self-medication, 11 studies show that the rate ranges from 6.2 to 42.3% ( Table 4 ). Mongolia has the highest rate (42.3%) ( 71 ) followed by those from Trinidad and Tobago ( 58 ) (33.1%), the US ( 70 , 114 ) (6.2–23.6%), China ( 96 , 97 , 101 , 111 ) (12.2–20.5%), the Republic of Macedonia ( 78 ) (17.8%), Saudi Arabia ( 110 ) (15.7%), and Lebanon ( 106 ) (6.5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study also suggested that managing patients with chronic cough is unduly time-consuming and expensive [ 33 ], suggesting improvements in practice and maybe attitudes. Previous studies reported data regarding the misdiagnosis and mistreatment status of cough in China, especially the overuse of antibiotics and overdiagnosis of chronic bronchitis [ [34] , [35] , [36] , [37] ], suggesting poor practice. Still, the present study is the first regarding the comprehensive KAP toward CRC in China.…”
Section: Discussionmentioning
confidence: 99%